2023
DOI: 10.3390/molecules28145389
|View full text |Cite
|
Sign up to set email alerts
|

New Acetamide-Sulfonamide-Containing Scaffolds: Antiurease Activity Screening, Structure-Activity Relationship, Kinetics Mechanism, Molecular Docking, and MD Simulation Studies

Abstract: The development of novel scaffolds that can increase the effectiveness, safety, and convenience of medication therapy using drug conjugates is a promising strategy. As a result, drug conjugates are an active area of research and development in medicinal chemistry. This research demonstrates acetamide–sulfonamide scaffold preparation after conjugation of ibuprofen and flurbiprofen with sulfa drugs, and these scaffolds were then screened for urease inhibition. The newly designed conjugates were confirmed by spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…It has already been reported that isoxazole substituted on the sulfonamide side and electron-withdrawing groups such as fluoro-substituted biphenyl groups on the acetamide side showed better urease inhibition activities as compared to methyl substituent phenyl groups on the acetamide side. Furthermore, guanidine and amino groups on the sulfonamide side showed excellent urease inhibition activities compared to five- and six-membered heterocyclic substituents. , Overall, the electron-withdrawing and -donating groups attached to phenyl groups play a pivotal role in the inhibition activities of urease enzymes. However, this effect largely depends on the overall structure of the molecule under investigation. , …”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…It has already been reported that isoxazole substituted on the sulfonamide side and electron-withdrawing groups such as fluoro-substituted biphenyl groups on the acetamide side showed better urease inhibition activities as compared to methyl substituent phenyl groups on the acetamide side. Furthermore, guanidine and amino groups on the sulfonamide side showed excellent urease inhibition activities compared to five- and six-membered heterocyclic substituents. , Overall, the electron-withdrawing and -donating groups attached to phenyl groups play a pivotal role in the inhibition activities of urease enzymes. However, this effect largely depends on the overall structure of the molecule under investigation. , …”
Section: Resultsmentioning
confidence: 91%
“…Furthermore, guanidine and amino groups on the sulfonamide side showed excellent urease inhibition activities compared to five-and six-membered heterocyclic substituents. 26,27 Overall, the electron-withdrawing and -donating groups attached to phenyl groups play a pivotal role in the inhibition activities of urease enzymes. However, this effect largely depends on the overall structure of the molecule under investigation.…”
Section: Structure−activity Relationship (Sar)mentioning
confidence: 99%
See 1 more Smart Citation
“…It facilitates the breakdown of urea into ammonia and carbamate, which is a biochemical process marking the end stage of nitrogen metabolism ( Naseer et al, 2022 ; Lin et al, 2012 ). It results in the alkylation effect (rise in pH); hence, it supports the survival of numerous pathogenic microorganisms in the host body ( Konieczna et al, 2012 ; Maier and Benoit, 2019 ; Ahmad et al, 2023 ). In humans, gastrointestinal infections are mostly caused by the alkaline pH, which leads to significant complications such as gastric ulcers and gastric cancer ( Sohrabi et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%